"Enzymatic" Photoreduction of Carbon Dioxide using Polymeric Metallofoldamers Containing Nickel–Thiolate Cofactors. Issue 7 (16th March 2017) - Thanneeru, Srinivas; Nganga, John K.; Amin, Alireza Shirazi; Liu, Ben; Jin, Lei; Angeles‐Boza, Alfredo M.; He, Jie
Abstract: The photoreduction of CO2 by using enzyme‐mimicking polymeric metallofoldamers containing Ni–thiolate cofactors was explored. Metallofoldamers consisting of folded polymers incorporated with Ni–thiolate complexes were prepared by intramolecular Ni–thiolate coordination with thiol‐functionalized linear copolymers. The folded polymer backbone may resemble the protein framework to provide a second coordination environment to the active sites. We showed that Ni–metallofoldamers were superiorly active and selective for CO2 photoreduction. At 80 °C, the turnover frequency of the Ni–metallofoldamers could reach 0.69 s −1, which corresponds to 2500 turnovers per hour per Ni site. Our findings are expected to provide useful guidelines to investigate artificial enzymes and to understand the role of protein frameworks in photosynthesis. Abstract : Hold 'em or fold 'em : Metallofoldamers consisting of folded polymers incorporating metal–thiolates are demonstrated to be highly active and selective for the photoreduction of CO2 .